A compact terahertz frequency selective surface with fast roll-off characteristics. (17th November 2022) - Ruan, Jiu Fu; Tao, Zhi; Zou, Rui Zhi; Meng, Zi Fan; Pan, Sheng Min
Abstract: A simple and compact terahertz frequency selective surface (FSS) with high selectivity is presented for cases of normal incidence. Guidelines for the design along with the operation mechanism are presented in detail from the view of an equivalent circuit. The design is implemented by mapping the lumped components of a microwave filter topology circuit with two transmission zeros to structures of the FSS; the mapping is realized by slotting a cross-shaped aperture in the grid. An intensive study on the equivalent circuit model predicts the existence of transmission zeros and poles. It can afford two transmission zeros and two transmission poles ranging from 350 GHz to 450 GHz with a band separation of 1.05 and 1.07, thereby exhibiting fast roll-off characteristics. The two transmission zeros can be controlled independently by simply changing the structure parameters of the unit cell. The proposed FSS is superior in terms of roll-off rate as well as the balance between selectivity and overall thickness. The measured results of the prototype are consistent with the simulation results, which validates the robustness of the design.